Identificação de raças fisiológicas de Colletotrichum lindemuthianum (Sacc et Magn) Scrib de três municípios do Estado do Espírito Santo - Resende Ribeiro , Solane; Martins Chaves , Geraldo (Revista Ceres, 2025)
Samples of bean pods (Phaseolus vulgaris) with anthracnose symptoms (Colletotrichum lindemuthianum) were collected in three counties of the state of Espírito Santo.